7/6-1/6x3/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 11/12 + 5/6 x 3/2 - 2/3
= 11/12 + 15/12 - 2/3
= 26/12 - 2/3
= 26/12 - 8/12
= 18 /12 = 3/2
b) 4/9 : 4/6 x 3/4 +5/3
= 4/9 x 6/4 x 3/4 + 5/3
= 2/3 x 3/4 + 5/3
= 6/12 + 5/3
= 6/12 + 20/12
= 26/12 = 13/6
c) 5/7 : 11/14 : 15/22 x 3/5
= 5/7 x 14/11 x 22/15 x 3/5
= 10/11 x 22/15 x 3/5
= 4/3 x 3/5 = 20/15 = 4/3
a. \(\dfrac{11}{12}+\dfrac{5}{6}\)x\(\dfrac{3}{2}-\dfrac{2}{3}\) \(=\)\(\dfrac{11}{12}+\dfrac{5}{4}-\dfrac{2}{3}=\dfrac{11}{12}+\dfrac{15}{12}-\dfrac{8}{12}=\dfrac{11+15-8}{12}=\dfrac{18}{12}=\dfrac{3}{2}\)
b. \(\dfrac{4}{9}:\dfrac{4}{6}\)x\(\dfrac{3}{4}+\dfrac{5}{3}\) \(=\dfrac{4}{9}:\dfrac{1}{2}+\dfrac{5}{3}=\dfrac{8}{9}+\dfrac{5}{3}=\dfrac{8}{9}+\dfrac{15}{9}=\dfrac{8+15}{9}=\dfrac{23}{9}\)
c. \(\dfrac{5}{7}:\dfrac{11}{14}:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{10}{14}:\) \(\dfrac{11}{14}:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{10}{11}\)\(:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{20}{22}:\dfrac{15}{22}\)x\(\dfrac{3}{5}\) \(=\dfrac{4}{3}\)x\(\dfrac{3}{5}=\dfrac{4}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a.
PT $\Leftrightarrow 3x^2+\frac{x}{2}-3x^2+3x+2=0$
$\Leftrightarrow \frac{7}{2}x+2=0$
$\Leftrightarrow \frac{7}{2}x=-2$
$\Leftrightarrow x=-2: \frac{7}{2}=\frac{-4}{7}$
b.
PT $\Leftrightarrow 5x^2-3-5x^2-6x=0$
$\Leftrightarrow -3-6x=0$
$\Leftrightarrow 6x=-3$
$\Leftrightarrow x=\frac{-3}{6}=\frac{-1}{2}$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{5}{6}\times3+\dfrac{20}{6}\times2-1:\dfrac{6}{5}\)
\(=\dfrac{5}{6}\times3-\dfrac{5}{6}+\dfrac{20}{6}\times2\)
\(=\dfrac{5}{6}\times\left(3-1\right)+\dfrac{20}{6}\times2\)
\(=\dfrac{5}{6}\times2+\dfrac{20}{6}\times2\)
\(=\left(\dfrac{5}{6}+\dfrac{20}{6}\right)\times2\)
\(=\dfrac{25}{6}\times2\)
\(=\dfrac{25}{3}\)
#DatNe
\(\dfrac{5}{6}\) \(\times\) 3 + \(\dfrac{20}{6}\) \(\times\) 2 - 1 : \(\dfrac{6}{5}\)
= \(\dfrac{5}{6}\) \(\times\) 3 + \(\dfrac{20}{6}\) \(\times\) 2 - \(\dfrac{5}{6}\)
= \(\dfrac{5}{6}\) \(\times\) 3 + \(\dfrac{5}{6}\) \(\times\) 8 - \(\dfrac{5}{6}\) \(\times\)1
= \(\dfrac{5}{6}\) \(\times\) ( 3 + 8 - 1)
= \(\dfrac{5}{6}\) \(\times\)10
= \(\dfrac{25}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Trl:
3 x 9 + 6 x 3 + 5 : 2 - 6 + 9 x 3 - 2
= 27 + 18 + 2,5 - 6 + 27 - 2
= 66,5
#HuyềnAnh#
Trl :
3 x 9 + 6 x 3 + 5 : 2 - 6 + 9 x 3 - 2
= 27 + 18 + 2,5 - 6 + 27 - 2
= 45 + 2,5 - 6 + 27 - 2
= 66,5
_ Jie _
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{3}{4}\times\dfrac{5}{7}=\dfrac{15}{28};\dfrac{5}{8}\times\dfrac{4}{15}=\dfrac{20}{120}=\dfrac{1}{6};\dfrac{7}{12}\times\dfrac{4}{9}=\dfrac{28}{108}=\dfrac{7}{27};\)
\(\dfrac{1}{6}\times\dfrac{3}{5}=\dfrac{3}{30}=\dfrac{1}{10};\dfrac{12}{21}\times\dfrac{23}{8}=\dfrac{276}{168}=\dfrac{23}{14};\dfrac{13}{4}\times\dfrac{5}{39}=\dfrac{65}{156}=\dfrac{5}{12}\)
\(\dfrac{7}{42}\times\dfrac{13}{21}=\dfrac{91}{882}=\dfrac{13}{126};\dfrac{3}{16}\times\dfrac{4}{15}=\dfrac{12}{240}=\dfrac{1}{20}\)
=11/12 nha bn
\(\frac{7}{6}\)\(-\frac{1}{6}\)x \(\frac{3}{2}\)
\(=\frac{7}{6}\)\(-\frac{3}{12}\)
\(=\frac{14}{12}\)\(-\frac{3}{12}\)
\(=\frac{11}{12}\)